CORRELATION BETWEEN PARITY AND PLACENTAL RETENTION INCIDENCE AT DR. SOEWANDHIE HOSPITAL, SURABAYA, INDONESIA - Mufidati, Diana; Soleha, Umdatus (Proceedings of the International Conference on Applied Science and Health, 2017)
Backgroud: The incidence rate of placental retention at Dr. Soewandhie Hospital Surabaya in January â April 2014 with the total labor involving 669 mothers, 28 laboring mothers (4.19%) experience placental retention. It can cause postpartum hemorrhage which becomes the leading cause to death. Aims: The purpose of this study was to find out the correlation between parity and the incidence of placental retention at Dr. Soewandhie Hospital Surabaya, Indonesia. Methods: The design of study was analytic-cross sectional. The population involved all laboring mothers in April 2014, totally 205 laboring mothers, in which 136 laboring mothers were taken as the samples by simple random technique. The data was secondary data from labor registration book. Then, the data was analyzed using Chi-Square .05. Results: The result of study showed that, 14.2% of the primiparous experienced placental retention, whilst multiparous and grand multiparous have higher proportion, reached to 42.9%. By the statistical analysis, we found that the correlation between parity and incidence of placental retention among the laboring mothers at Dr. Soewandhie Hospital Surabaya, Indonesia, was significant (p value = 0,008). Conclusion: It can be concluded that the more parity, the higher the risk of placental retention. It shows in urgency at Dr. Soewandhie Hospital Surabaya to provide counseling and education about the ideal number of children and increasing acceptance of family planning.Â